Proteomic changes of the bovine blood plasma in response to heat stress in a tropically adapted cattle breed - Henrique Goncalves Reolon; Natalya Gardezani Abduch; Natalya Gardezani Abduch; Ana Claudia de Freitas; Ana Claudia de Freitas; Rafael Medeiros de Oliveira Silva; Breno de Oliveira Fragomeni; Daniela Lourenco; Fernando Baldi; Claudia Cristina Paro de Paz; Claudia Cristina Paro de Paz; Nedenia Bonvino Stafuzza (Frontiers Media SA, 2024)
BackgroundIdentifying molecular mechanisms responsible for the response to heat stress is essential to increase production, reproduction, health, and welfare. This study aimed to identify early biological responses and potential biomarkers involved in the response to heat stress and animal’s recovery in tropically adapted beef cattle through proteomic analysis of blood plasma.MethodsBlood samples were collected from 14 Caracu males during the heat stress peak (HSP) and 16 h after it (heat stress recovery—HSR) assessed based on wet bulb globe temperature index and rectal temperature. Proteome was investigated by liquid chromatography-tandem mass spectrometry from plasma samples, and the differentially regulated proteins were evaluated by functional enrichment analysis using DAVID tool. The protein-protein interaction network was evaluated by STRING tool.ResultsA total of 1,550 proteins were detected in both time points, of which 84 and 65 were downregulated and upregulated during HSR, respectively. Among the differentially regulated proteins with the highest absolute log-fold change values, those encoded by the GABBR1, EPHA2, DUSP5, MUC2, DGCR8, MAP2K7, ADRA1A, CXADR, TOPBP1, and NEB genes were highlighted as potential biomarkers because of their roles in response to heat stress. The functional enrichment analysis revealed that 65 Gene Ontology terms and 34 pathways were significant (P < 0.05). We highlighted those that could be associated with the response to heat stress, such as those related to the immune system, complement system, hemostasis, calcium, ECM-receptor interaction, and PI3K-Akt and MAPK signaling pathways. In addition, the protein–protein interaction network analysis revealed several complement and coagulation proteins and acute-phase proteins as important nodes based on their centrality and edges.ConclusionIdentifying differentially regulated proteins and their relationship, as well as their roles in key pathways contribute to improve the knowledge of the mechanisms behind the response to heat stress in naturally adapted cattle breeds. In addition, proteins highlighted herein are potential biomarkers involved in the early response and recovery from heat stress in tropically adapted beef cattle.
Keywords: Caracu; beef cattle; potential biomarkers; pathways; Genetics; liquid chromatography-tandem mass spectrometry; QH426-470; Bos taurus taurus; 2. Zero hunger